A CULTURA DO CONFLITO E A CULTURA DO DIÁLOGO NO ÂMBITO DA SUPERLOTAÇÃO DO JUDICIÁRIO - DE PAULA, Maria Vitória Chaves Carvalho Leonel de Paula; SILVA, Elisabeth Maria de Mendonça (ANAIS DO ENIC, 2025)
.